2016
DOI: 10.5455/ijmsph.2016.01032016435
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid dysfunction in the patients visiting Tertiary Health Care Hospital, Firozabad; Uttar Pradesh

Abstract: Background: Thyroid disorders (hypothyroidism and hyperthyroidism) are a widespread thyroid problem, but there are no reports on the incidence and prevalence of thyroid disorders in this part of Western Uttar Pradesh of India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The thyroid disorders are more common in female than male. [10,11,12] It may due to hormonal change, such as during or after pregnancy or after menopause. Sex hormones, especially estrogen and prolactin, have an important role in modulating the immune system and may impact autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…The thyroid disorders are more common in female than male. [10,11,12] It may due to hormonal change, such as during or after pregnancy or after menopause. Sex hormones, especially estrogen and prolactin, have an important role in modulating the immune system and may impact autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, overall prevalence of hypothyroid was found to be 36.07% which is closer to 38% [29] and also 43%. [39] The prevalence of hypothyroid may vary 1-38%. [40][41][42] Overall prevalence of hyperthyroid in our study constitutes 5% of the total population.…”
Section: Discussionmentioning
confidence: 99%
“…T3 & T4. According to WHO (World Health Organization) recommendation, daily 150μm iodine intake is required for men, non-pregnant females and non-lactating females; 250μm for both pregnant & lactating females; 90μm for 0-59 months old (preschool) children and 120μm for 6-12 years old (school going) children 12 .…”
Section: Introductionmentioning
confidence: 99%